Improved cold‐water detergency of malodourous soil correlating with hydrophilic–lipophilic deviation concept. Issue 2 (12th November 2021) - Phaodee, Parichat; Adamy, Steven T.; Zehr, Robert T.; Harwell, Jeffrey H.; Grady, Brian P.
Abstract: The persistence of sebum after low‐water‐temperature washing can contribute to malodor and microbial growth during subsequent use; thus, this work focuses on improved sebum removal. The detergency of sebum at various hydrophobic–lipophilic deviation (HLD) values was performed using 0.1 w/v% C12‐13 ‐8PO‐SO4 Na and C8 ‐4PO‐1EO‐SO4 Na at 1:1 molar ratio. The detergency of synthetic sebum on 87/13 polyester/spandex was relatively poor (70% removal) at HLD = 0. Various additives (heptanol, dipropylene glycol n‐butyl ether, decyltrimethyl ammonium bromide or sodium benzoate) were explored and it was found that none of them could facilitate sebum removal on the 87/13 polyester/spandex surface. On the other hand, adding low molecular weight primary amines (ethylene diamine, or monoethanolamine [MEA]) in the surfactant system without salt showed sebum removal of 70%–80% depending on the amine molecule. Adding MEA as a detergency additive with salt appeared to achieve good detergency (>80% removal) at all studied HLD numbers between −1.0 and 1.1 and the maximum detergency (approximately 90% removal) was observed at the optimum formulation (HLD = 0). The formulation pH with added MEA decreased from 11 to roughly 9. Detergency performance with added MEA was not dependent on pH within the studied basic conditions. The principal cold water sebum removal mechanism was found to be detachment of solid sebum fractions, dispersed in the detergent bath or floating on the bath surface.